Conductive films based on sandwich structures of carbon nanotubes/silver nanowires for stretchable interconnects - Jheng, Li-Cheng; Hsiao, Chi-Hui; Ko, Wen-Ching; Hsu, Steve Lien-Chung; Huang, Yu-Lun (My University, 2019)
A variety of conductive films made of a hybrid of two conductive nanomaterials have been used as stretchable electrodes or interconnectors, desirable for stretchable electronic devices. Their intrinsic stretchability of electrical conductivity allows for accommodating mechanical strain to a certain extent under various deformations. However, few efforts have been made to enhance the interactions between two conductive components in a hybrid system. Herein, we reported new conductive films with tri-layer sandwich structures based on carbon nanotubes (CNTs) and Ag nanowires (NWs), encapsulated in silicone rubber, exhibited high stretchability along with insignificant piezoresistivity. They are suitable to be stretchable interconnectors. A successive vacuum filtration method was used to stack the conductive components layer by layer. The effects of the stacking sequence and the interactions between layers on the stretchability and stability of the electrical properties under mechanical deformations were studied. In the case of a tri-layer conductive film comprising two CNT outer layers and one AgNW central layer in the presence of enhanced interfacial interactions, it showed exceptionally durability in withstanding repetitive deformations.
Keywords: stretchable electronics; silver nanowires; carbon nanotubes; hybrid; sandwich structure